Mapping MHC Genes in River Buffalo - Rodrigues Filho, E. A. [UNESP]; Stafuzza, N. B. [UNESP]; Caetano, A. R.; Gill, C. A.; Riggs, P. K.; Womack, J. E.; Amaral, M. E. J. [UNESP] (Karger, 2008)
The major histocompatibility complex (MHC) contains a set of genes necessary for antigen presentation in the immune system. This gene dense and polymorphic region of the mammalian genome is of considerable interest due to the role of MHC genes in immune function and animal health. Previous cytogenetic studies have indicated that the MHC in river buffalo resides on the short arm of chromosome 2 (BBU2). A 5000-rad radiation hybrid mapping panel was recently generated to enable construction of a whole genome map of river buffalo. To this and, the aims of this project were to elucidate the general organization of the MHC on BBU2, and to compare gene order within this region to the MHC in cattle. PCR primers were selected from the bovine gene map and used with the BBURH(5000) panel to map a set of ten MHC class 11 genes in river buffalo. Analysis indicates that these genes fall into two linkage groups, consistent with organization of the MHC in cattle. This comparison of buffalo and bovine MHC gene order provides the first insight into the organization of the MHC on river buffalo chromosome 2.
Keywords: MHC genes; RH mapping; BBU2p; River buffalo